An Algorithm for Consolidating Small Shipments to Reduce Costs in International Logistics for E-commerce Businesses - Tovstolis, Igor (International Journal of Supply Chain and Logistics, 2024)
Purpose: This article presents an algorithm designed to optimize the consolidation of small shipments, aiming to reduce costs and improve efficiency in international logistics for e-commerce businesses. The research focuses on the highly trafficked route between China and the USA, particularly the corridor from Shenzhen to Los Angeles. Methodology: By employing a cluster-based optimization model, the algorithm consolidates goods from multiple e-commerce companies into single containers, maximizing space utilization and minimizing transportation costs. Findings: Experimental data reveals a 40% reduction in costs and a 10-day decrease in delivery times compared to traditional methods. Unique Contribution to Theory, Practice and Policy: The algorithm has the potential as a scalable solution for global supply chain logistics.